Degradation of PET – Quantitative estimation of changes in molar mass using mechanical and thermal characterization methods - Gernot Oreski; Bettina Ottersböck; Chiara Barretta; Petra Christöfl; Simone Radl; Gerald Pinter (Polymer Testing, 2023)
Polyethylene terephthalate (PET) films are used when mechanical strength, thermal and chemical stability, and barrier properties to atmospheric gases are required in combination with good processability. Hydrolysis leading to embrittlement of the material is a major concern as PET is used in a variety of applications with expected lifetimes of up to decades (e.g., for use in buildings, textiles, or photovoltaic backsheets). Therefore, a comprehensive understanding of the degradation processes and the effects on the molecular mass distribution is of great importance.Usually, the direct determination of molar mass and molar mass distribution involves high effort and sophisticated equipment. Therefore, the main objective of this work is to quantify molar mass changes due to accelerated aging using thermal and mechanical methods. Two stabilized PET films were subjected to seven different accelerated aging conditions (heat; combined heat-humidity). The samples were then characterized by size exclusion chromatography (SEC), tensile tests and differential scanning calorimetry (DSC).A linear correlation was found between crystallization temperature and average molar mass. The values of fracture stress from tensile tests indicate a ductile-brittle transition at a molar mass of 15 000 g mol−1. The study concludes that the crystallization temperature obtained from DSC measurements can be used to estimate changes in the average molar mass of PET after hydrolysis. Crystallization temperatures between 208 °C and 211 °C correspond to a critical reduction in molar mass and severe embrittlement.